Optimalisasi Pengelolaan Keuangan UMKM melalui Digitalisasi Pencatatan Transaksi Harian - Septiani, Dwi; Ferdiansyah, Ferdiansyah; Sunarto, Sunarto (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to improve financial literacy and technical skills of MSME actors in recording daily transactions using the Microsoft Excel application. The program employed a participatory approach through three main stages: preparation, implementation, and evaluation. The partner for this activity was Happy Fresh Frozen Food, Bogor Branch, an MSME that previously lacked a structured and sustainable financial recording system. The stages of the program included initial coordination and development of training materials, technical training on the use of Microsoft Excel accompanied by transaction recording simulations, and evaluation through observation, discussion, and post-tests analyzed using descriptive qualitative methods. The results of the program indicated that business owners began to understand the importance of transaction recording, are able to use the provided Microsoft Excel templates, and have demonstrated increased discipline in financial documentation. These findings suggest that simple digital tools can serve as transformative solutions for MSMEs in building effective and independent financial administration systems. Furthermore, the program contributes to fostering a culture of financial discipline and prepares MSMEs to face future business formalization challenges.